Exercise Intensity and Lymphocyte Subset Apoptosis - Navalta, J. W.; Lyons, S.; Prestes, J.; Arnett, S. W.; Schafer, M.; Sobrero, G. L. (International Journal of Sports Medicine, 2013)
This investigation assessed the lymphocyte subset response to increasing intensity. Participants completed an exertion test (VO2max), and later performed a 10-min run at 76% VO2max, 5-min at 87%, and run to exhaustion at 100% intensity. Blood was sampled at rest, following each intensity, and 1-h post. Cell concentration, apoptosis (annexin V) and migration (CX3CR1) were evaluated in CD4+, CD8+, and CD19+ subsets. Relative data were analyzed using 1-way ANOVA with significance at P≤0.05. Absolute changes from rest (Δ baseline) were calculated for exercise conditions. CX3CR1 displayed relative changes 1-h post, (CD8+ Pre=58%, Post=68%, 1 h-Post=37%, P=0.04) (CD19+ Pre=1.9%, Post=3.2%, 1 h-Post=5.2%, P=0.02). No relative changes were noted for subsets and annexin V. Absolute changes revealed that CD4+/annexin V+ and CD8+/annexin V+ significantly increased at 76%,(P<0.01). Significant absolute increases were observed in CD4+/CX3CR1 at 87% VO2max, and at 87% and 100% VO2max in CD8+/CX3CR1 (P<0.01). Subsets respond differently with intensity with respect to cell count, and markers of apoptosis and cell migration. CD4+ and CD8+ appear to be prone to apoptosis with moderate exercise, but significant increases in migration at higher intensities suggests movement of these cells from the vasculature in postexercise measurements.
Keywords: leukocyte subfractions; lymphocytosis; programmed cell death; fractalkine; muscular activity; annexin V